Developing Digital Greetings using Adobe Animate - Haoyu Zhang; Zhuowei Wang (CV TOPAZART, 2023)
Greeting is an act of communication in which human beings intentionally make their presence known to each other, to show attention to, and to suggest a type of relationship. Expressing best wishes for someone, sending gifts or even sending a special message. However, the current life style in the IT era may shift sending message style. For them, smartphones and other digital media are more interesting than mail. This paper is intended to create a mobile-based greeting which contains a small game. Developing the application, the researcher conducts qualitative approaches of Multimedia Development Life Cycle (MDLC) that contains 6 stages, concept, design, obtaining content material, assembly, testing, and distribution. It is the utmost hope that the new IT-based greetings model could facilitate easier, more fun and interesting especially for children and youth. This research is still on going and the researcher would like to present a smartphone-based greetings model. Research findings show that mobile-based greetings including games is the most feasible model to send as a greeting message through WhatsApp and WeChat.